The Used of Concrete Objects in Mathematics to Increase Students' Interest in Learning - Nisa, Khairun; Rokhmana, Siti; Rakhmana, Patra Aghtiar (Universitas PGRI Sumatera Barat, 2023)
The problem at hand is that many people say that math is difficult learning and there are still many lessons that do not use learning media using concrete objects, resulting in monotonous learning and students are not interested or enthusiastic about learning. Therefore, there is a need for concrete object media in the learning process to increase students' interest in learning. The purpose of this study was to find out by using concrete objects media in learning mathematics can increase students' interest in learning. This research uses descriptive method. The subject of this research is the 2nd grade teacher of SDN Sumampir and data collection was carried out by interview. The result of this research is that by using concrete objects media in the mathematics learning process can make colorful learning not monotonous and can increase students' interest in learning.